Pengaruh Konseling dan Leaflet terhadap Efikasi Diri, Kepatuhan Minum Obat, dan Tekanan Darah Pasien Hipertensi di Dua Puskesmas Kota Depok - Dewanti, Sri Wahyuni; Andrajati, Retnosari; Supardi, Sudibyo (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2015)
Self-efficacy and low adherence was significant problem on using antihypertension drugs. The study purpose was to evaluate the effectiveness of counseling and provision of leaflets againts self-efficacy and adherence as well as the blood pressure of hypertensive patients at two community health centers in Depok City. The study desain is a quasi-experimental with 37 patients in counseling group and 36 patients in the leaflets group during March to June 2013. The instrument determine self-efficacy is MUSE scale, MMAS-8 scale for adherence and the tensimeter for blood pressure. Data were analyzed uses the Wilcoxon and Kolmogorov-Smirnov test. The results showed that the largest percentage of hypertension patients in community health centers have mild hypertension, has been suffering from hypertension between 1-5 years, received a single drug, mostly captopril, and did not feel any side effects. The counseling and provision of leaflets can increase self-efficacy and medication adherence, and lower systolic blood pressure significantly. Provision of leaflets to patients can increase self-efficacy and adherence, and lowering the systolic and diastolic pressure significantly. There is no significant difference between the effects of counseling and the provision of leaflets to increase self-efficacy and adherence, as well as a decrease in blood pressure in hypertensive patients in community health centers in Depok City